Sport as An Entrepreneurial Activity and Possibility of Selfinancing Throughout Crowdfunding Platforms (Vallis Aurea, 2018)
Sport is recognized as an area of a great importance for society and national economy. It is evolving into a profitable entrepreneurial activity and marketable activity. There are numerous ways of sports financing. In the context of the modern economy, there is a need to develop models of sports self-financing. As an emerging form of financing, crowdfunding changes the way in which entrepreneurs collect money for financing their business projects in various business activities starting from social entrepreneurship and software development towards entertainment industry. Sport is not an exception to this trend. Due to its potential to influence and change traditional financial flows and to change traditional principles of financial intermediations, crowdfunding has drawn attention of scientists and practitioners who are trying to explain what could be consequences, risks, development phases and future trends in this field. In this paper, firstly, we draw attention to the need and perception of sports self-financing in the sample of future entrepreneurs in Croatia based on conducted primary research. Secondly, we give definition, development and types of crowdfunding activities in the context of entrepreneurial self-financing. Then, based on the case study analysis method, we outline several successful examples of self-financing sports projects in developed markets in order to explain and illustrate potentials of crowdfunding as a financing source in sports.